2005
DOI: 10.1007/bf02706351
|View full text |Cite
|
Sign up to set email alerts
|

Structural morphology of amorphous conducting carbon film

Abstract: Amorphous conducting carbon films deposited over quartz substrates were analysed using X-ray diffraction and AFM technique. X-ray diffraction data reveal disorder and roughness in the plane of graphene sheet as compared to that of graphite. This roughness increases with decrease in preparation temperature. The AFM data shows surface roughness of carbon films depending on preparation temperatures. The surface roughness increases with decrease in preparation temperature. Also some nucleating islands were seen on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 22 publications
2
7
0
Order By: Relevance
“…However, extraction of hydrogen described by reactions ͑14͒-͑16͒ requires a significant amount of heat; this may lead to a less significant increase in the surface diffusion rates. The significance of the surface diffusion effect in this temperature range is consistent with the results of Vishwakarma et al 42 When the surface temperature is sufficiently high to maintain reasonably high rates of hydrogen extraction and surface diffusion, high-quality carbon nanostructures are expected. 43 Meanwhile, higher rates of dehydrogenation reactions may lead to a larger number of adsorption sites for the carbonaceous ions; this further enhances the growth of the CNTPs.…”
Section: Effect Of Surface Temperaturesupporting
confidence: 89%
“…However, extraction of hydrogen described by reactions ͑14͒-͑16͒ requires a significant amount of heat; this may lead to a less significant increase in the surface diffusion rates. The significance of the surface diffusion effect in this temperature range is consistent with the results of Vishwakarma et al 42 When the surface temperature is sufficiently high to maintain reasonably high rates of hydrogen extraction and surface diffusion, high-quality carbon nanostructures are expected. 43 Meanwhile, higher rates of dehydrogenation reactions may lead to a larger number of adsorption sites for the carbonaceous ions; this further enhances the growth of the CNTPs.…”
Section: Effect Of Surface Temperaturesupporting
confidence: 89%
“…It has been observed that the morphology varies with the variation of RF power. Formation of different surface morphologies like circular, granular, linear, and other structures have also been reported by many authors [21][22][23][24]. Formation of different structures depend on the process parameters like bias voltage, gas composition, type of power supply and power used.…”
Section: Resultsmentioning
confidence: 61%
“…The high internal stress limits the DLC films for various applications. Correlation of internal stress with sp 3 /sp 2 bonded carbon and various properties have been studied by many authors [21][22][23][24]. While the correlation between surface structures and sp 2 /sp 3 bonded carbon has not been investigated extensively.…”
Section: Related Workmentioning
confidence: 99%
“…One of the most predominant defects in the graphite structure is the formation of sp 3 bonds [8][9][10]. The position and intensity of each band (G or D) will determine the characterization of carbon coating [8]. While these bands overlap, in order to determine the band intensity, the spectra are deconvoluted by Lorentzian method.…”
Section: Resultsmentioning
confidence: 99%
“…The former is related to sp 2 bonds and graphite structure (G band) and the later is related to in-planar defects in graphite structure (D band). One of the most predominant defects in the graphite structure is the formation of sp 3 bonds [8][9][10]. The position and intensity of each band (G or D) will determine the characterization of carbon coating [8].…”
Section: Resultsmentioning
confidence: 99%